Sentinel Monitoring Program: Quality Assurance in Laboratory animal facility (Journal of Laboratory Animal Science, 2018)
Sentinel animal testing plays a pivotal role in management of any modern vivarium. It is an extremelyuseful tool to assess the microbial status of the laboratory animals as part of the comprehensive animalcare program. Sentinels pick up the early infection if any, in the micro and/or macro environment, as theseanimals are placed in a similar environment intentionally. Sentinels are representative animals, independentof the research colonies and are maintained only for the purpose of screening the pathogenic organismsat regular intervals. At times, as part of 3R's, we have on occasion used research animals to confirm oursentinel results. Sentinel program is concerned with prompt detection of pathogens and the measuresto deal with them thereby ensuring the health status of the resident colony. With an effective sentinelmonitoring program preventive measures can be taken to enact either, treat, contain or eradicate thepathogen. This review provides insights into the sentinel program with respect to disease surveillance oflaboratory animals and conveys why it is necessary for effective in laboratory animal program management
Keywords: agents,; sentinel program; , health monitoring,; test methods; serology, culture; polymerase chain reaction (PCR), enzyme-linked immunosorbent assay (ELISA); immunofluoresence Assay (IFA